GANYONG (CANNA EDULIS), YANG TERABAIKAN MENJADI BENTENG KANKER USUS BESAR - Ismawardika, Alifiani; Larasandi, Deasy; Sadid, Ahmad; Fiolita, Redita Elva; Prayoga Griadhi, Nyoman Odiyana (Program Kreativitas Mahasiswa - Penelitian, 2013)
Background : Colorectal cancer is one of the most common cancer that can lead to mortality. Since  patients come in the late stage, mostly they have bad prognosis. Thus, prevention is the most effective way to decrease the mortality and morbidity. Ganyong (Canna edulis) is plant which the root contains of high fiber and calcium which are good to prevent colorectal cancer. Aim : This experiment is conducted to examine the preventive effect of ganyong solution to the development of colorectal cancer. Method : The research design is experimental with using of post test only with control group design method. 30 male Wistar rats weighing 100-120 gram (4 week of age) are used in this experiment. The rats are devided into 6 groups randomly and each group consists of 5 rats. Group 1 got AOM/DSS only While, AOM/DSS, coconut oil and ganyong solution are given to the group 2. Then group 3 got AOM/DSS and ganyong solution and group 4 got AOM/DSS and coconut oil. Group 5 got coconut oil and ganyong solution. And group 6 which is negative control group got aquadestIndependent t test is used to analyse the data. Result: Macroscopically, the amount of rats that have nodule in G2 (75%) is lesser than G4 (100%). Microscopically, there are 3 rats from G1 having adenokarsinoma while only 2 rats from G3 having same thing. Statistically this difference is significant (p>0,05). Conclusion : Ganyong can decrease the number of nodule in group which was given coconut oil. And  microscopically it can effective in preventing the tumor development in group without coconut oil.   Keyword : Canna edulis, colorectal cancer , prevention